2014
DOI: 10.1371/journal.pone.0115900
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Tobacco Smoking and Cessation among HIV-Infected Individuals under Care in Rio de Janeiro, Brazil

Abstract: Worldwide the prevalence of smoking among people living with HIV/AIDS is elevated compared to the general population. This probably reflects the cluster of individual characteristics that have shared risk factors for HIV infection and smoking. A cross-sectional study, enrolling a convenience sample from a Brazilian HIV clinical cohort was conducted to evaluate the prevalence of tobacco smoking and the factors associated with current smoking and abstinence. A total of 2,775 HIV-infected individuals were intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 59 publications
4
19
0
8
Order By: Relevance
“…As the disease approaches the status of a manageable chronic condition, other risk factors, such as eating habits physical activity, alcohol use, treatment of hypertension, diabetes, socio-demographic characteristics and the effects of aging start to play a more important role for the health status in this population. In addition, chronic exposure to medication [ 7 11 ], higher prevalence of smoking [ 12 ], metabolic syndrome [ 13 ] and HCV-coinfection [ 14 ] are other important factors that could be linked to increased risk of CVD in this population.…”
Section: Introductionmentioning
confidence: 99%
“…As the disease approaches the status of a manageable chronic condition, other risk factors, such as eating habits physical activity, alcohol use, treatment of hypertension, diabetes, socio-demographic characteristics and the effects of aging start to play a more important role for the health status in this population. In addition, chronic exposure to medication [ 7 11 ], higher prevalence of smoking [ 12 ], metabolic syndrome [ 13 ] and HCV-coinfection [ 14 ] are other important factors that could be linked to increased risk of CVD in this population.…”
Section: Introductionmentioning
confidence: 99%
“…To account for a large number of participants with missing CD4 + T lymphocyte counts (n = 442) and HIV-1 RNA levels (n = 429), a sensitivity analysis was conducted using the aforementioned statistical methods for participants with both CD4 + T lymphocyte counts and HIV-1 RNA levels (n = 576). Guided by previous findings, 33 colinearity between 90-day crack/cocaine use and 90-day tobacco use was tested. When it was found, tobacco was excluded from regression models.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of urban GBMSM have also found smoking rates to be higher and cessation rates lower in HIV-positive men (Robinson et al, 2014). People living with HIV/AIDS (PLWHA) who smoke are at elevated risk for several comorbid conditions including pulmonary infectious diseases, cancer, cardiovascular disease, and tuberculosis (Helleberg et al, 2015; Torres et al, 2014). Further, PLWHA who smoke report lower treatment adherence, higher viral load counts, and are less likely to attend routine medical visits (O’Cleirigh et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of this research has been cross-sectional (e.g., Gamarel et al, 2015; Lifson et al, 2010; Levinson et al, 2012; Newcomb et al, 2014; O’Cleirigh et al, 2015a; Robinson et al, 2014; Torres et al, 2014; Tron et al, 2013) and almost none have adopted a longitudinal design. Cross-sectional studies in the United States found that 45–72% of GBMSM report attempted cessation in the previous year, and preparation to quit was associated with daily (vs. non-daily) smoking, having a smoke-free home, asking a doctor for advice, and having used nicotine replacement therapy (Levinson et al, 2012; Robinson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%